CONCEPT AND STRUCTURE OF LEGAL TERMINOLOGY (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
Legal terminology is a collection of special terms and concepts used in the legal field. It is one of the main elements of the legal system and plays an important role in legal communication and preparation of legal documents. Legal terminology also helps express legal concepts clearly and concisely, which increases the efficiency of legal processes. A legal term is a special word or phrase that expresses a legal concept. For example, terms such as "contract", "property", "liability" are examples of legal terms. A legal concept is a meaning or content expressed by a legal term. Concepts are the main elements of the legal system, and their interactions determine legal relations. The Rules of Legal Terminology are a set of rules for how to use and explain legal terms. These rules ensure clarity and clarity in the preparation of legal documents and legal communication. These are terms that represent the basic concepts of the legal field. For example, terms such as "right", "duty", "property", "responsibility". Legal terminology includes terms that express social and legal relations. These relationships are the main elements of the legal system. Legal terminology also includes terms representing legal norms. For example, terms such as "constitution", "law", "decision". Each legal field has its own special terms. For example, in criminal law there are terms such as "crime", "punishment", "victim".Legal terminology ensures clear and unambiguous communication, which increases the efficiency of legal processes. Terminology plays an important role in the preparation of legal documents. Clear terms ensure accuracy and legality of documents. Legal terminology is important in legal education. Pupils and students use terminology in learning legal concepts. Legal terminology is also important in international legal communication. Terminology is necessary to clearly express legal concepts between different countries.